Overview of Therapeutic Inertia in Diabetes: Prevalence, Causes, and Consequences - Karam, Susan L. (Diabetes Spectr, 2020)
Many people with diabetes do not achieve individualized treatment targets. Therapeutic inertia, the underuse of effective therapies in preventing serious clinical end points, is a frequent, important contributor to this failure. Clinicians, patients, health systems, payors, and producers of medications, devices, and other products for those with diabetes all play a role in the development of therapeutic inertia and can all help to reduce it.